The Constant Gardener - Bøggild, Jacob; Holm, Jens Henrik (K&K - Kultur og Klasse, 2006)
Om kampen om anerkendelse og den artige revolution i H. C. Andersens »Gartneren og Herskabet« The Constant Gardener H. C. Andersen’s tale »The Gardener and the Royal Family« appears to be one of his very straightforward ones, the irony in it of a satirical and therefore stable kind. Moreover, it seems obvious that the tale is an allegory about the miscredited artist, one such as Andersen conceived himself to be, as well as about the political changes in Denmark in the latter part of the 19th century. Still, it has engendered conflicting views amongst its critics. This fact has prompted Ib Johansen to hail it as a »strong« text in the sense of Harold Bloom. This article expands on Johansen’s view in seeking to tease out in what aspects of the text this strength might be grounded. The answer we offer is that it is grounded in the figure of the gardener, who reamains a blank surface, so to speak, and subsequently represents a radical openness to interpretation. This, we further argue, brackets the aforementioned possibilities for an allegorical reading of one or the other kind. Previous readings by Peer E. Sørensen, Johan de Mylius and Ib Johansen are discussed in the process. Furthermore, we discover the Hegelian dialectic between the master and the slave to be an operative force in the text. What comes forth, we believe, is an added awareness of the specific nature of the revolutionary force of Andersen’s irony, measured also in contrast to the irony of another tale of his, »The Storm Shifts the Sideboards«, even in a case where it, at a first glance, appears to be of a facile and easily decipherable kind.